Ethyl ferulate, a lipophilic phenylpropanoid, prevents diabetes‐associated renal injury in rats by amelioration of hyperglycemia‐induced oxidative stress via activation of nuclear factor erythroid 2‐related factor 2. Issue 4 (15th February 2021) - Kaikini, Aakruti Arun; Muke, Suraj; Peshattiwar, Vaibhavi; Bagle, Sneha; Dighe, Vikas; Sathaye, Sadhana
Abstract: Diabetic nephropathy affects approximately 20%–40% of diabetes patients worldwide and is the leading cause of end‐stage renal failure. Oxidative stress has been identified as a major causative factor in the development and progression of diabetic nephropathy; Nuclear factor erythroid 2‐related factor 2 (Nrf2) activation protects the body against oxidative stress by induction of antioxidant enzymes. The renoprotective effect of ethyl ferulate was investigated in diabetes‐induced renal injury. Ethyl ferulate was administered orally at three doses (50 mg/kg, 75 mg/kg, and 100 mg/kg). Metformin (500 mg/kg, p.o .) was used as a standard. Ethyl ferulate treatment decreased serum advanced glycation end products, glycosylated hemoglobin (HbA1c) levels, renal oxidative stress, tumor necrosis factor‐α (TNF‐α) level, and kidney hypertrophy index. It restored serum lipid profile, biomarkers of renal function, and mitigated histopathological signs of renal damage. Immunohistochemistry demonstrated higher Nrf2 protein levels in kidney sections of ethyl ferulate‐treated rats. These findings suggest that ethyl ferulate ameliorated hyperglycemia‐induced oxidative stress by increasing renal Nrf2 levels, thereby preventing diabetes‐induced kidney injury. In conclusion, the present study endorses the usefulness of Nrf2 activators, such as ethyl ferulate, as adjuvant therapy for preventing the diabetic nephropathy. Practical applications: Ethyl ferulate (ethyl‐3‐hydroxyl‐4‐methoxycinnamate), a phenylpropanoid, is a naturally occurring ethyl ester of ferulic acid and is widely present in plants and especially grains, such as rice and maize. Our study has highlighted the renoprotective effect of ethyl ferulate in preventing diabetes‐associated renal injury. The observed effect of ethyl ferulate is due to amelioration of diabetes‐induced oxidative stress and inflammation, by activation of the Nrf2 pathway. These results indicate the potential of ethyl ferulate as a nutraceutical or adjuvant therapy in prevention of diabetic nephropathy. Abstract : Hyperglycemia‐induced oxidative stress is a major key player in the pathogenesis of diabetes‐associated renal damage. Nuclear factor erythroid 2‐related factor 2 (Nrf2), a transcription factor for antioxidant enzymes, acts as endogenous defense system and protects the body against oxidative stress. Kidney tissues of diabetic rats demonstrated oxidative stress, low Nrf2 protein levels, inflammation, and injury. Ethyl ferulate prevented diabetic renal injury by ameliorating hyperglycemia‐induced oxidative stress via Nrf2 activation.